2009
DOI: 10.1098/rstb.2008.0288
|View full text |Cite
|
Sign up to set email alerts
|

Talent in the taxi: a model system for exploring expertise

Abstract: While there is widespread interest in and admiration of individuals with exceptional talents, surprisingly little is known about the cognitive and neural mechanisms underpinning talent, and indeed how talent relates to expertise. Because many talents are first identified and nurtured in childhood, it can be difficult to determine whether talent is innate, can be acquired through extensive practice or can only be acquired in the presence of the developing brain. We sought to address some of these issues by stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 56 publications
2
45
0
Order By: Relevance
“…Converging evidence from studies in rodents and humans suggests that experiencedependent development also plays a critical role in modulating development of neural wiring and regional specialization processes (1,2,16). For instance, studies have shown that behavioral training shapes intrinsic characteristics, such as volume, morphometry, myelination, and local circuits, in task-relevant brain structures (30,31). Similar principles are likely to operate in the BLA and CMA, leading to increased segregation of function within these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Converging evidence from studies in rodents and humans suggests that experiencedependent development also plays a critical role in modulating development of neural wiring and regional specialization processes (1,2,16). For instance, studies have shown that behavioral training shapes intrinsic characteristics, such as volume, morphometry, myelination, and local circuits, in task-relevant brain structures (30,31). Similar principles are likely to operate in the BLA and CMA, leading to increased segregation of function within these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Because all the Baduk experts recruited for this study also started training very young, it is possible that innate factors influenced our selection of the Baduk experts. Along these lines, a report on the navigating talents of London taxi drivers attributed these skills to extensive training during adulthood (Woollett et al, 2009). Using voxelbased measures on structural brain MRI data, the authors revealed that the expertise acquired in adulthood can cause significant changes in gray matter volume as well as in neuropsychological profiles.…”
Section: Hemispherementioning
confidence: 98%
“…However, it is impossible to resist asking, could we all be savants if only we put in the hours of practice? Woollett et al (2009) show that navigation expertise rests on years of training and even then depends on constant practice. London taxi drivers who have internalized the complex street map of London show concomitant changes in the hippocampus.…”
Section: Hours Of Practicementioning
confidence: 99%